2004
DOI: 10.1073/pnas.0400930101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes that synergize with Cbfb-MYH11 in the pathogenesis of acute myeloid leukemia

Abstract: Acute myeloid leukemia subtype M4 with eosinophilia is associated with a chromosome 16 inversion that creates a fusion gene CBFB-MYH11. We have previously shown that CBFB-MYH11 is necessary but not sufficient for leukemogenesis. Here, we report the identification of genes that specifically cooperate with CBFB-MYH11 in leukemogenesis. Neonatal injection of Cbfb-MYH11 knock-in chimeric mice with retrovirus 4070A led to the development of acute myeloid leukemia in 2-5 months. Each leukemia sample contained one or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 44 publications
5
110
0
Order By: Relevance
“…Polycythemia vera (PV), a myeloproliferative neoplasm (MPN), is characterized by the presence of a mutated, activated form of the tyrosine kinase JAK2. 1 In 95% of cases, PV patients present the V617F mutation in exon 14 (JAK2-V617F) and half of V617F-negative PV patients carry mutations or deletions in exon 12. 2 Both types of mutations result in activation of JAK2 and STAT5.…”
Section: Flt3-itd (81%) and Flt3-tkd (83%mentioning
confidence: 99%
See 1 more Smart Citation
“…Polycythemia vera (PV), a myeloproliferative neoplasm (MPN), is characterized by the presence of a mutated, activated form of the tyrosine kinase JAK2. 1 In 95% of cases, PV patients present the V617F mutation in exon 14 (JAK2-V617F) and half of V617F-negative PV patients carry mutations or deletions in exon 12. 2 Both types of mutations result in activation of JAK2 and STAT5.…”
Section: Flt3-itd (81%) and Flt3-tkd (83%mentioning
confidence: 99%
“…However, knock-in mouse models have demonstrated that CBFB-MYH11 alone is not sufficient to cause a leukemic phenotype and that additional aberrations were essential for the development of AML. 1 Secondary cytogenetic abnormalities occur in B40% of cases with þ 22, þ 8 (10-15% each), and del(7q) or þ 21 is most commonly observed. Recent molecular analyses have also provided important insights into the pathogenesis of myeloid disorders, and the commonly detected mutations of KIT and NRAS genes as well as deregulated CEBPA expression have been identified as likely candidates for cooperating events in CBF-positive AML.…”
mentioning
confidence: 99%
“…Interestingly, a retroviral genetic screen, involving neonatal injection of Cbfb-MYH11 knock-in chimeric mice with retrovirus 4070A followed by analysis of the insertion sites, has identified Plag1 and Plagl2 among the genes which independently cooperate with CBFB-MYH11 fusion gene in leukemogenesis (Castilla et al, 2004). AML subtype M4 with eosinophilia is associated with a chromosome 16 inversion that creates a fusion gene CBFB-MYH11, encoding CBFbeta-SMMHC fusion protein.…”
Section: Chromosomal Deletion and Rearrangementmentioning
confidence: 99%
“…Runt-related transcription factor-2 regulation and transcriptional activity are linked with increased growth, invasion, and metastasis in breast cancer (Barnes et al, 2003), prostate cancer (Brubaker et al, 2003;Pratap et al, 2005), colorectal cancer (Wai et al, 2006), lymphoma, leukaemia and myeloma (Wotton et al, 2002;Castilla et al, 2004;Colla et al, 2005;Blyth et al, 2006).…”
mentioning
confidence: 99%